Study of Science Philosophy: Behavioral Bias and Investment Decisions - Andhi Wijayanto; Mugi Harsono (Management Analysis Journal, 2022)
bjectives This paper aims to develop a theoretical and research framework by identifying behavioral biases in investment decisions and reviewing the existing literature in the field of behavioral biases related to behavior finance from the perspectives of ontology, epistemology, and axiology. This is because behavioral biases in management, and in particular financial management, remain an interesting research area. The study by Parveen, Satti, and Bashir (2021) demonstrates that heuristics and behavioral biases do exist and impact the decisions made by Pakistani investors during COVID-19. Pakistani investors have suffered a loss due to their faulty thinking. The Pakistani stock market exhibited features of dual process theory and prospect theory throughout this outbreak. Investors can employ both gut feelings and rational analysis. Since this study illuminates the impact of COVID-19 on emerging stock markets like Pakistan's, it contributes to the expanding body of scholarship on behavioral finance in developing nations.